Polystyrene Microplastics Induced Ovarian Toxicity in Juvenile Rats Associated with Oxidative Stress and Activation of the PERK-eIF2α-ATF4-CHOP Signaling Pathway - Wanzhen Wang; Jiafu Guan; Yueying Feng; Shanji Liu; Yu Zhao; Yuanyuan Xu; Hengyi Xu; Fen Fu (Toxics, 2023)
Numerous reports confirm that microplastics exposure could induce reproductive toxicity in mammals. However, the effects of microplastics exposure during juveniles on ovarian apoptosis through oxidative and endoplasmic reticulum (ER) stresses remains unclear, which is the focus of our study. In the present study, female rats (4 weeks old) were exposed to polystyrene microplastics (PS-MPs, 1 μm) at different dosages (0, 0.5, and 2.0 mg/kg) for 28 days. Findings revealed that 2.0 mg/kg of PS-MPs distinctly increased the atretic follicle ratio in the ovary and dramatically reduced the serum levels of estrogen and progesterone. Additionally, the oxidative stress indicators declined, including the activity of superoxide dismutase and catalase, whereas the malondialdehyde content in the ovary was considerably enhanced in the 2.0 mg/kg PS-MPs group. Furthermore, the expressions of genes related to ER stress (PERK, eIF2α, ATF4, and CHOP) and apoptosis were remarkably elevated in the 2.0 mg/kg PS-MPs group compared with those in the control group. We found that PS-MPs induced oxidative stress and activated the PERK-eIF2α-ATF4-CHOP signaling pathway in juvenile rats. Moreover, with the oxidative stress inhibitor N-acetyl-cysteine and eIF2α dephosphorylation blocker Salubrinal treatment, ovarian damage induced by PS-MPs was repaired and associated enzyme activities were improved. Overall, our results indicated that PS-MPs exposure induced ovarian injury associated with oxidative stress and activation of the PERK-eIF2α-ATF4-CHOP signaling pathway in juvenile rats, providing new prospects for assessing the health risks of children exposed to microplastics.